A new multigene HCIQ subfamily from the sea anemone Heteractis crispa encodes Kunitz-peptides exhibiting neuroprotective activity against 6-hydroxydopamine - Kvetkina, Aleksandra; Leychenko, Elena; Chausova, Victoria; Zelepuga, Elena; Chernysheva, Nadezhda; Guzev, Konstantin; Pislyagin, Evgeny; Yurchenko, Ekaterina; Menchinskaya, Ekaterina; Aminin, Dmitry; Kaluzhskiy, Leonid; Ivanov, Alexis; et al. (Scientific reports, 2020)
The Kunitz/BPTI-type peptides are ubiquitous in numerous organisms including marine venomous animals. The peptides demonstrate various biological activities and therefore they are the subject of a number of investigations. We have discovered a new HCIQ subfamily belonging to recently described multigene HCGS family of Heteractis crispa Kunitz-peptides. The uniqueness of this subfamily is that the HCIQ precursors contain a propeptide terminating in Lys-Arg (endopeptidase cleavage site) the same as in the neuro- and cytotoxin ones. Moreover, the HCIQ genes contain two introns in contrast to HCGS genes with one intron. As a result of Sanger and amplicon deep sequencings, 24 HCIQ isoforms were revealed. The recombinant peptides for the most prevalent isoform (HCIQ2c1) and for the isoform with the rare substitution Gly17Glu (HCIQ4c7) were obtained. They can inhibit trypsin with K i 5.2 × 10 −8 M and K i 1.9 × 10 −7 M, respectively, and interact with some serine proteinases including inflammatory ones according to the SPR method. For the first time, Kunitz-peptides have shown to significantly increase neuroblastoma cell viability in an in vitro 6-OHDA-induced neurotoxicity model being a consequence of an effective decrease of ROS level in the cells.